Educational Activities of Universities in The Field of Physical Education of The Republic of Uzbekistan - A. N. Normuradov (Web of Journals Publishing, 2023)
The article examines the educational activities of universities in the field of physical education of the Republic of Uzbekistan.
Keywords: qualimetry, educational activities, management, qualities, components, criteria, indicators.